Plant breeding for harmony between agriculture and the environment. Issue 10 (14th September 2011) - Brummer, E Charles; Barber, Wesley T; Collier, Sarah M; Cox, Thomas S; Johnson, Randy; Murray, Seth C; Olsen, Richard T; Pratt, Richard C; Thro, Ann Marie
Abstract : Plant breeding programs primarily focus on improving a crop's environmental adaptability and biotic stress tolerance in order to increase yield. Crop improvements made since the 1950s – coupled with inexpensive agronomic inputs, such as fertilizers, pesticides, and water – have allowed agricultural production to keep pace with human population growth. Plant breeders, particularly those at public institutions, have an interest in reducing agriculture's negative impacts and improving the natural environment to provide or maintain ecosystem services (eg clean soil, water, and air; carbon sequestration), and in creating new agricultural paradigms (eg perennial polycultures). Here, we discuss recent developments in, as well as the goals of, plant breeding, and explain how these may be connected to the specific interests of ecologists and naturalists. Plant breeding can be a powerful tool to bring "harmony" between agriculture and the environment, but partnerships between plant breeders, ecologists, urban planners, and policy makers are needed to make this a reality.